Development Of The Marketing Reciprocal Value Concept For Msme Performance - Andriyansah Andriyansah; Fatia Faimah; Emiliana Sri Pudjiarti (UNIVED Press, 2024)
The purpose of the research is to find out whether there are other strategies that can be done by companies to maintain and improve their performance. Three things that become important points of this research are the inconsistency in the implementation of strategies that can improve and even reduce the Company's performance, but other indications of business competition performance assessment show positive signals of the movement of the Indonesian business world. Researchers suspect that there are other strategies besides innovation that can improve performance. using a qualitative approach by exploring various literacies related to reciprocal. In addition, to support the research results, this study uses reliable respondents with the criteria being MSME actors who have run their businesses for 2 years. This research found a reciprocal concept that can improve the performance of MSMEs. Novelty in this research includes Reciprocity of Pricing, Reciprocity of Skill and Reciprocity of value product. The concept found is expected to improve relations between business people, the agreement between business people can improve the marketing performance of MSMEs.